GLOBALIZATION OF HIGHER EDUCATION: EXPERIENCE OF THE SCHOOL OF GEOGRAPHIC SCIENCES, NATIONAL UNIVERSITY, COSTA RICA - Araya-Ramírez, Iliana; Quirós-Arias, Lilliam; Ruíz-Hernández, Amalia (Revista Geográfica de América Central., 2016)
The experience of globalization and international cooperation is analyzed based on three indicators: tools for cooperation, academic activities, and the products and academic results from joint activities. In the School of Geographical Sciences at the National University (UNA), Geography has had a footprint in the process of globalization. The international cooperation efforts by the National University have promoted the development of a solid and updated geography in the new theoretical and methodological approaches along with prestigious universities from Brazil, Mexico, Argentina, Chile, Colombia, as well as the traditional cooperation with countries such as the United States, Canada and Spain.